1990
DOI: 10.1073/pnas.87.10.3977
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor-dependent disruption of a specific nucleosome on the mouse mammary tumor virus promoter is prevented by sodium butyrate.

Abstract: Our laboratory has previously developed cell lines derived from mouse NIH 3T3 fibroblasts and C127 mammary tumor cells that stably express mouse mammary tumor virus (MMTV) long terminal repeat fusion genes in bovine papillomavirus-based episomes. Glucocorticoid hormone strongly activates transcription from episomes and induces the disruption of a single nucleosome in an array of phased nucleosomes on the MMTV promoter. Sodium butyrate inhibits the glucocorticoid hormone-dependent development of a nuclease-hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 45 publications
5
77
0
Order By: Relevance
“…The data represent the results of three independent experiments. (c) Histones were extracted from cells treated for the times indicated with TSA and subjected to Western blotting with antibodies against acetylated H3 and H4 (Bresnick et al, 1990;Bartsch et al, 1996;Lambert and Nordeen, 1998), there is also a strong inhibition of basal (control) transcription, an observation also reported by Bartsch et al (1996). Transcription of the b-actin gene was not significantly changed by these TSA treatments ( Figure 1a and data not shown).…”
Section: Effects Of Tsa On Mmtv Transcriptionmentioning
confidence: 64%
See 2 more Smart Citations
“…The data represent the results of three independent experiments. (c) Histones were extracted from cells treated for the times indicated with TSA and subjected to Western blotting with antibodies against acetylated H3 and H4 (Bresnick et al, 1990;Bartsch et al, 1996;Lambert and Nordeen, 1998), there is also a strong inhibition of basal (control) transcription, an observation also reported by Bartsch et al (1996). Transcription of the b-actin gene was not significantly changed by these TSA treatments ( Figure 1a and data not shown).…”
Section: Effects Of Tsa On Mmtv Transcriptionmentioning
confidence: 64%
“…Previous studies examining regulation of the MMTV promoter by HDAC inhibitors found that, depending on a variety of conditions, butyrate or TSA could activate or repress the MMTV promoter in organized chromatin (Bresnick et al, 1990;Bartsch et al, 1996;Lambert and Nordeen 1998;Myers et al, 1998;Wilson et al, 2002). Repression was observed in seven distinct cell lines with two exceptions.…”
Section: Effects Of Tsa On Mmtv Transcriptionmentioning
confidence: 92%
See 1 more Smart Citation
“…The 3617 cell line was stably transfected with a Flag-tagged BRG1-K-R to generate the 5555 cell line. The 1365.1 cell line is derived from NIH 3T3 mouse fibroblast cells by stable transformation with a multicopy episome and contains multiple tandem copies of a stably integrated MMTV-LTR array (Cordingley et al, 1987;Bresnick et al, 1990). Human adrenal carcinoma cells (SW13) are deficient in BRG1, BRM, and GR expression and were obtained from the American Type Culture Collection (ATCC, Manassas, VA).…”
Section: Cell Culture and Stable Cell Linesmentioning
confidence: 99%
“…Acetylation of core histones regulates transcription of many promoters, including MMTV (Struhl, 1998). Sodium butyrate, which induces histone hyperacetylation, inhibits glucocorticoid hormone-dependent nucleosome disruption and promoter activation from an MMTV template assembled as chromatin (Bresnick et al, 1990). However, glucocorticoid activation from a transiently introduced MMTV template was una ected.…”
Section: Gr and Other Transcriptional Coactivatorsmentioning
confidence: 99%